THE CONTENT OF MORAL EDUCATION OF CHILDREN AND THE FORMATION OF MORAL QUALITIES (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article examines the essence and content of moral education in children, focusing on the development of moral qualities as a foundation for responsible and ethical behavior. It highlights the key stages, methods, and psychological-pedagogical principles that ensure the successful formation of moral values in childhood. The study draws on classical and contemporary pedagogical theories to outline effective strategies for fostering virtues such as honesty, empathy, responsibility, and respect for others. The findings demonstrate that a systematic approach to moral education contributes significantly to the holistic development of children and the formation of a harmonious personality.